The Music of man. - Menuhin, Yehudi, 1916-1999 (Home Vision, 1987)
The influences in the development of music from the Middle Ages to the Renaissance. Medieval plainsong of the Christian Church contributed a reliable system of notation and led to the development of harmony. In addition, Jewish, Islamic and Indic music added elements to our musical heritage.